2020
DOI: 10.12968/jowc.2020.29.sup2c.s4
|View full text |Cite
|
Sign up to set email alerts
|

The safety of punch biopsies on hard-to-heal wounds: a large multicentre clinical trial

Abstract: Objective: Punch biopsy is a simple and effective diagnostic technique used in hard-to-heal wound management. Histologic examination can rule out cancer in the wound bed or diagnose vasculitis in a hard-to-heal or suspicious ulcer. A biopsy can determine the level of bacteria in an ulcer when infection is suspected. Despite its use, health professionals practicing in wound clinics hesitate to perform punch biopsies. The reasons vary from the invasive nature of the procedure to a fear of complications. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
2
3
0
Order By: Relevance
“…No serious adverse event resulting from use of the device was reported. 42 In 82% (287/350) of wounds, bacterial loads >10 4 CFU/g were observed, confirmed by microbiological analysis (Fig. 3).…”
Section: Resultssupporting
confidence: 63%
“…No serious adverse event resulting from use of the device was reported. 42 In 82% (287/350) of wounds, bacterial loads >10 4 CFU/g were observed, confirmed by microbiological analysis (Fig. 3).…”
Section: Resultssupporting
confidence: 63%
“…Serena et al 5 reported on postoperative complications in a large multicenter clinical trial involving 412 skin biopsies for intractable skin ulcers using a 6-mm punch and found no significant difference in postoperative bleeding between patients receiving anticoagulation and those not receiving anticoagulation, similar to the results of our study.…”
Section: Discussionsupporting
confidence: 90%
“…In this consideration, rodents, like mice or rats, or even big mammalian animals, like pigs, were reported as good models to examine the skin wound-healing process and mechanism [6,70,71]. Moreover, there are some techniques that make use of more advanced tools, such as clinical dermatology lasers and biopsy punches, to investigate wound healing [11,14,23,26]. However, the clinical dermatology laser is relatively expensive and might be unaffordable to many laboratories.…”
Section: A Laser Engraving Machine-based Methods Has Been Established...mentioning
confidence: 99%
“…However, this method is usually only performed in cells, as it is used to examine the cell migration of cells. Meanwhile, modern wound-healing experiments utilize more advanced tools, such as the biopsy punch and dermal laser [23][24][25][26][27]. The challenge for skin wound-healing experiments in fish is how to control the depth and size of the wound in a consistent manner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation